Effects of controlled atmosphere, edible coating, and 1-methylcyclopropene on improving storage quality of 'Bartlett' pears after long-term storage. Issue 1 (2nd January 2019) - Zhi, Huanhuan; Dong, Yu; Wang, Yan
ABSTRACT: Recent trends towards greater fresh market use of 'Bartlett' pears has increased the need to extend its storage life to prolong the packing and marketing season in the United States Pacific Northwest region. Sixteen and 38%, respectively, of control fruit developed senescence disorders following 5 and 6 months of storage at −1.1°C. Commercial standard controlled atmosphere (CA) conditions (O2 at 1.5 kPa and CO2 < 1 kPa) or edible coating (Semperfresh™, SF) prevent the appearance of senescence disorders for 5 months, but 9% and 16% of fruit, respectively, developed senescence disorders after 6 months. The combination of CA+SF completely inhibited senescence disorders for 6 months. Treatment with CA and SF, alone or in combination, maintained high-storage quality and developed ripening capacity with characteristic melting texture during storage. Senescence disorders were inhibited for 6 months by 0.3 µL l −1 1-methylcyclopropene (1-MCP), alone or combination with CA or CA+SF. In part these pears developed ripening capacity after 6 months of storage. The combination of CA+SF+1-MCP maintained the highest storage quality with dark green colour and hard firmness, which might be associated and proportional with reductions in ethylene synthesis and respiration rate after long-term storage.